2013
DOI: 10.1093/infdis/jit667
|View full text |Cite
|
Sign up to set email alerts
|

HIV Antibody Characterization as a Method to Quantify Reservoir Size During Curative Interventions

Abstract: Quantitative humoral profiling of recent samples from a human immunodeficiency virus (HIV)-infected adult who was cured following a delta32/delta32 CCR5 stem cell transplant in 2007 revealed no antibodies against p24, matrix, nucleocapsid, integrase, protease, and gp120, but low levels of antibodies against reverse transcriptase, tat, and gp41. Antibody levels to these HIV proteins persisted at high and stable levels in most noncontrollers, elite controllers, and antiretroviral-treated subjects, but a rare sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 15 publications
4
58
0
Order By: Relevance
“…Although routine antibody tests to confirm HIV-status cannot be recommended in this population, the strong relationship between cumulative viral load and anti-gp120 IgG levels, support a possible role for antibody quantification to assess extent of virological control or reservoir size[30]. These assays might also be used to improve clinical management since high HIV-antibody quantity or seropositivity after early-ART could be a marker of poor adherence, inappropriate dose, drug absorbance/metabolism issues, or these factors combined.…”
Section: Discussionmentioning
confidence: 99%
“…Although routine antibody tests to confirm HIV-status cannot be recommended in this population, the strong relationship between cumulative viral load and anti-gp120 IgG levels, support a possible role for antibody quantification to assess extent of virological control or reservoir size[30]. These assays might also be used to improve clinical management since high HIV-antibody quantity or seropositivity after early-ART could be a marker of poor adherence, inappropriate dose, drug absorbance/metabolism issues, or these factors combined.…”
Section: Discussionmentioning
confidence: 99%
“…The avidity and concentration of HIV antibodies appears to change with declining numbers of latently infected cells 91 and markers of T cell activation and proliferation have been shown to correlate with the number of latently infected cells in multiple studies 29 .…”
Section: Novel Biomarkers To Analyse/quantify Hiv Reservoirsmentioning
confidence: 99%
“…Table 7 summarizes the prevalence and isotype/subclass distribution of antibody responses against non-Env proteins. The most frequently recognized targets are structural p17, p24 and pol -derived p31 and p66 ( table 7 ) [27,48,126,[143][144][145][146] . In fact, diagnostic tests, such as confirmatory Western blot, are based on the additional detection of p17, p24 and p31-specific IgG (e.g.…”
Section: Igg Subclass Distribution Of Env-specific Antibodies During mentioning
confidence: 99%
“…For example, it has been shown that p17, p24 and PR-specific antibodies were associated with nonprogression or a stable clinical status [45,144,145,152,160] . On the other hand, p31-specific antibodies were found to be associated with a worse prognosis, and results obtained for Tat-and Vprspecific responses were controversial ( table 7 ) [45,46,[146][147][148]155] . The use of antibody reactivity patterns as prognostic markers has not yet been established for the clinical practice.…”
Section: Igg Subclass Distribution Of Env-specific Antibodies During mentioning
confidence: 99%